Ergonomi Kemudi Kapal dengan Pendekatan Antropometri - Andi Hendrawan; Aji K. Hendrawan; Priyani Budiarti; Altril Rayendra (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2024)
The steering system is one of the components that must be present on a ship, because the determination of the desired direction is controlled by this system. On the rudder there is a rudder blade and a rudder stock. The importance of the role of the ship's rudder in the sailing process so that it is necessary to analyze the working position of the ship's driver in order to minimize the risk of musculoskeletal disorders. The study was conducted by observing several prospective captains in the Nusantara Maritime Academy Cilacap simulator laboratory. The analysis was conducted using the Rapid Entire Body Assessment (REBA) and Anthropometry approaches. The results of the study showed that a worker's working position is an important thing to consider in order to create comfort in working and reduce the risk of injury such as musculoskeletal disorders. Analysis of ship steering operators in the Nusantara Maritime Academy Cilacap simulator room using REBA (Rapid Entire Body Assessment) produced a value of 4, so it can be concluded that the working position is at a moderate risk level and needs improvement. The proposed design for improving ship steering in the Nusantara Maritime Academy Cilacap simulator room uses anthropometric references carried out on 30 cadets. Measurements of body dimensions and percentiles applied as references for the proposed design of the ship's steering room are produced as follows: (1) the 50th percentile is used for the size of eye height (eye view height at the ship's window), elbow (throttle lever height and steering wheel handle height from the floor), hip height (steering wheel height from the floor), (2) the 5th percentile is used for the size of Dgmin (throttle lever diameter) and Dgmak (steering wheel diameter).